2015
DOI: 10.1063/1.4906508
|View full text |Cite|
|
Sign up to set email alerts
|

Momentum resolution in inverse photoemission

Abstract: We present a method to determine the electron beam divergence, and thus the momentum resolution, of an inverse-photoemission setup directly from a series of spectra measured on Cu(111). Simulating these spectra with different beam divergences shows a distinct influence of the divergence on the appearance of the Shockley surface state. Upon crossing the Fermi level, its rise in intensity can be directly linked with the beam divergence. A comparison of measurement and simulation enables us to quantify the moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…5(d) shows the surface resonance (SR) and the bulk states labeled as B1 and B2. The spectra are in qualitative agreement with earlier studies [58][59][60] though with lower signal/noise ratio. The E(k) dispersion extracted from Fig.…”
Section: B Spin Polarization Resolutionsupporting
confidence: 91%
See 1 more Smart Citation
“…5(d) shows the surface resonance (SR) and the bulk states labeled as B1 and B2. The spectra are in qualitative agreement with earlier studies [58][59][60] though with lower signal/noise ratio. The E(k) dispersion extracted from Fig.…”
Section: B Spin Polarization Resolutionsupporting
confidence: 91%
“…The spin asymmetry there from the down-to-up intensity ratio at k ↓ F /k ↑ F is ∼ 1.6. Since Zumbülte et al 59 demonstrated that the intensity ratio between k ↑ F and k ↓ F is proportional to the electron beam divergence, in our case we have an angular divergence of ∆θ = ±3.0 • . The angular divergence can be also estimated by considering the spot diameter at the decelerator lens (410 µm) and at the sample, having ∆θ = ±2.3 • .…”
Section: Wavevector Resolutionmentioning
confidence: 52%
“…The detector has a Sherman function of S = 0.24 [30]. For spin-resolved IPE, we use a spin-polarized electron source, which provides an electron beam of 3 mm diameter with a spin polarization of P = 0.29 [33] and a beam divergence of about ±2 • [34]. For non-normal electron incidence on the sample, our setup is sensitive to the out-of-plane spin component [33].…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…counter at E = 9.8 eV [44]. The overall IPE energy resolution was 350 meV and the angular resolution ±2 • [45].…”
Section: Discussionmentioning
confidence: 99%